A Conceptual Model For The Interplay Among Digital Transformation, Information System Quality, The Use Of E-Kinerja Application, And State Civil Apparatus Work Productivity - Elizah, Tenti; Permanasari, Revi; Ifnaldi, Ifnaldi; Apriani, Eka (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
This research aimed to develop a conceptual model examining the interplay among digital transformation, information system quality, the use of E-Kinerja application and State Civil Apparatus (SCA) work productivity. As the foregoing, this research deployed four variables which were drawn into a conceptual model by formulating six hypotheses. This research used the Partial Least Squares Structural Equation Modeling approach to frame the model and statistically testing it. 250 SCAs (both lecturers and staff at IAIN Curup) were involved as the respondents because they had adequate experiences regarding the use of E-Kinerja application. Data were collected using valid and reliable questionnaires. Using Smart PLS 4 program, the data were analyzed to evaluate the developed conceptual model. The analysis results demonstrated that digital transformation positively influenced SCA Work productivity (H1) with a path coefficient of 0.202 and T-statistics of 4.696. The impacts of digital transformation on the use of E-Kinerja application (H2) and on the quality of information systems (H3) were very strong, with path coefficients of 0.330 and 0.690 respectively, and very high T-statistics. The influence of information system quality on the use of E-Kinerja application (H4) was also significant with a coefficient of 0.637 and T-statistics of 18.300. Even though the direct influence of information system quality on SCA work productivity (H5) was more moderate, the significance value still showed that information system quality played a vital role in supporting efficient work productivity. Finally, a very prominent result was the influence of using the E-Kinerja application on SCA Work productivity (H6), with a coefficient of 0.589 and T-statistics of 6.572. The forgoing data demonstrated that the developed model was well-confirmed empirically. This research highlights that a well-designed application for work management, such as E-Kinerja, when supported by the implementation of digital transformation and information system quality, can enhance employeesâ€™ work productivity.Â  Future research is expected to examine moderating factors that can influence the effectiveness of digital transformation.